Social Media Penetration and Voter Turnout in Southeast Asia: A Multi-Country Comparative Study Using Public Survey Data - Elinda Novita Dewi; Muhammad Nurfaizi Arya Rahardja; Ayu Ambarwati; Bustomi Bustomi; Wan Muna Marwah; Moh. Imron Rosidi; Anjela Karunia Amalia (International Journal of Applied Research and Innovation, 2026)
This study examines the relationship between social media penetration and voter turnout in Southeast Asia using a multi-country comparative design based on publicly available survey data. Drawing on cross-national evidence, the analysis shows that social media access is associated with higher voter turnout, but only under specific political, institutional, and social conditions. Countries with competitive elections, higher institutional trust, and credible information environments display stronger turnout effects linked to social media use, while contexts characterized by patronage-based mobilization and political uncertainty show weaker or uneven outcomes. The study further demonstrates that campaign strategies on social media shape participation through personalization, network-based diffusion, and emotional framing, often mobilizing particular voter segments rather than the electorate as a whole. Social inequalities in education, income, gender, and civic capacity significantly moderate these effects, limiting the participatory gains of digital expansion for marginalized groups. Overall, the findings suggest that social media acts as a conditional amplifier of electoral participation rather than a universal driver of voter turnout in Southeast Asia.